2022
DOI: 10.13052/jcsm2245-1439.1133
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of Routine Activity Theory’s Applicability in Cybercrimes

Abstract: Cybercrimes are increasing at an alarming rate and cause detrimental effects to the victims. Routine Activity Theory (RAT) is commonly used to understand the factors influencing cybercrime victimization. However, there have been inconsistent findings on the applicability of RAT theory. This study performs a Systematic Literature Review analysis to consolidate and provide a coherent analysis of the related studies employing RAT theory for cybercrime victimization. The articles were also differentiated based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…Thus, RA 9995 was an essential law everyone should know. However, challenges like improving the knowledge and investigative skills among police officers and educators need to be emphasized (Paek et al, 2021;Ahmad & Ramayah, 2022). Additionally, socioeconomic factors like income, education level, and access to technology can affect the risk of cybercrime and people's awareness of specific laws (Mupila et al, 2023).…”
Section: Level Of Awareness Of the Respondents Toward The Anti-voyeur...mentioning
confidence: 99%
“…Thus, RA 9995 was an essential law everyone should know. However, challenges like improving the knowledge and investigative skills among police officers and educators need to be emphasized (Paek et al, 2021;Ahmad & Ramayah, 2022). Additionally, socioeconomic factors like income, education level, and access to technology can affect the risk of cybercrime and people's awareness of specific laws (Mupila et al, 2023).…”
Section: Level Of Awareness Of the Respondents Toward The Anti-voyeur...mentioning
confidence: 99%
“…Prior research has shown that engaging in cyber social media activities, for example, sharing personal information on social media, increases the risk of cybercrime victimization (Choi and Lee, 2017; Ahmad and Thurasamy, 2022). Specifically, participating in risky cyber leisure activities and vocational activities significantly influences cybercrimes victimization, such as cyber interpersonal violence victimization (Choi and Lee, 2017) and cyberbullying victimization (Choi et al , 2019).…”
Section: Routine Activities Theory Revisitedmentioning
confidence: 99%
“…Even cybercrime gains a wealthy attention of SLR publications, such as dark and surface web cybercrime intelligence threat (Cascavilla et al , 2021), routine activity theory in cybercrime (Ahmad and Thurasamy, 2022), cybercrime legislation (Khan et al , 2022), cybercrime defensive mechanism in virtual currency (Badawi and Jourdan, 2020), cybercrime investigation standard operating procedure (Jeffries and Apeh, 2020), cyberattacks during COVID-19 (Chigada and Madzinga, 2021), cybercrime fear (Brands and Van Doorn, 2022), cybercriminal profiling (Bada and Nurse, 2021), situational crime prevention techniques (Ho et al , 2022), social media cybersecurity (Herath et al , 2022) and cybersecurity frameworks (Perwej et al , 2021). Unfortunately, very few published articles elaborate the concern of money mule from a scholarly perspective.…”
Section: Introductionmentioning
confidence: 99%